Real-time microscopic study and modeling of the disruption of bacterial swarming motion - Lu, Shengtao (2016)
Collective motion of living organisms is ubiquitous in nature. In biology, certain bacteria such as the Gram-positive Bacillus subtilis can differentiate into swarming cells and move rapidly across the surface of a semisolid media in multicellular rafts or clusters. Experimental studies on the collective motion of bacteria have so far been limited to understanding the swarming dynamics of healthy cells. In this work the motion dynamics of disrupted swarming bacteria is studied and modeled: i) The collective motion of Bacillus subtilis in the presence of a photosensitizer is disrupted by reactive oxygen species when exposed to light of sufficient dosages and is partially recovered when light irradiation is suspended. The transition from a highly collective to a more random motion is modeled using an improved self-propelled model with alignment rule. ii) Monolayer of swarming Bacillus subtilis on semi-solid agar display elevated resistance against antibiotics. The drug resistance is impeded when the collective motion of bacteria is judiciously disrupted using non-toxic polystyrene (PS) colloidal particles immobilized on the agar surface. The colloidal particles block and hinder the motion of the cells, causing cohesive rafts of bacteria to lose their collectivity and speed. The negative correlation between the degree of collectivity and PS particle density is examined using an improved self-propelled model that takes in to account inter-particle alignment and hard-core repulsion.